Lhokseumawe City Government's Contribution in Handling Brawls - Lisa Fadila; Mugni, Abdul (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2023)
Brawls between teenagers in Lhokseumawe City have disturbed the community. This has caused concern and unrest for the prospective future generation of this nation. Therefore, this article will explore the what and how, as well as explain the contribution of the Lhokseumawe City government. A deep analysis of the root causes of the brawl will be the starting point for formulating the right solution as an alternative in handling the brawl. The results of the analysis showed that the factors causing the brawl include; Group offence, liquor, disputes, persecution, land grabs.